Production and characterization of monoclonal antibodies against GII.6 norovirus virus-like particles. (May 2020) - Qiu, Shuxing; Zheng, Lijun; Qin, Chuan; Yin, Xing; Ma, Jie; Liu, Jinjin; Yang, Zhaojie; Li, Chunwei; Wang, Yumei; Wang, Mingchen; Qi, Yonghua; Huo, Yuqi
Abstract: In this study we generated and characterized a series of monoclonal antibodies (mAbs) against GII.6 norovirus (NoV) virus like particles (VLPs). Mice were immunized with purified GII.6 NoV VLPs and peptide-bovine serum albumin (BSA) conjugates with the peptide sequence (31 aa) derived from the trypsin cleavage region. An indirect enzyme-linked immunosorbent assay was used to identify positive cell clones during cloning and subcloning, and an in vitro VLP-histo-blood group antigens (HBGAs) binding blockade assay was used to identify mAbs with blocking ability. A total of seven mAbs comprising five (1F7, 1F11, 2B6, 2C4, and 2E10) reactive with major capsid proteins (VP1) and two (1E5 and 2B2) reactive with both VP1 proteins and the peptide were identified. mAb 1F7, 1F11, and 2B6 were identified as blocking antibodies. Sandwich ELISA indicated that all these mAbs recognized soluble GII.6 NoV VLPs. Cross-reactivities with GI.7, GII.3, and GII.4 NoV VLPs were observed in indirect and sandwich ELISA. Western blot analysis indicated that all non-blocking mAbs recognized denatured GII.6 VP1 proteins and blocking mAbs only recognized non-denatured proteins. The in vitro VLP-HBGA binding blockade assay indicated that the three blocking antibodies exhibited blocking effects against GII.6 NoV VLPs, but not GI.7, GII.3, and GII.4 NoV VLPs. Epitope mapping and HBGA blocking assay indicated that mAbs targeting the predicted surface-exposed loop region did not have blocking effects, suggesting a possible important role of this region in regulating NoV-HBGA interactions. This is the first report regarding the characterization of mAbs with blocking ability against GII.6 NoV VLPs. These mAbs might be useful in facilitating our understanding of this group of viruses. Highlights: Monoclonal antibodies with histo-blood group antigens (HBGAs) blocking effects against GII.6 Norovirus were identified. Monoclonal antibodies targeting the surface-exposed loop region did not have HBGAs blocking effects. Blocking monoclonal antibodies only recognized conformational epitopes. The surface exposed loop region might have important role in regulating NoV-HBGAs interactions.